ChemInform Abstract: A New Megastigmane Glucoside and Three New Flavonoid Glycosides from Spiraea prunifolia var. simpliciflora. Issue 9 (March 2015) - Yean, Min Hye; Kim, Ju Sun; Kang, Sam Sik; Kim, Yeong Shik
Abstract isolation and structure elucidation of a new megastigmane glucoside, simplicifloranoside (I) and three new flavonol glycosides, prunifolianosides A—C (II)